A review of the hazardous effects of polycyclic aromatic hydrocarbons on living organisms - Marin-Morales, Maria Aparecida [UNESP]; Leme, Daniela Morais [UNESP]; Mazzeo, Dânia Elisa Christofoletti [UNESP] (My University, 2009)
Polycyclic aromatic hydrocarbons (PAHs) are one of the most important, abundant and dangerous class of persistent organic contaminants found in air, water, food and waste sites. The great concern with this class of pollutants is due to the fact that these chemicals cause various deleterious effects, which could jeopardize the genome of exposed organisms or even lead them to death. Many studies have been conducted in several laboratories distributed around the world and with different organisms to quantify the impact of those pollutants and to diagnose their action mechanisms. Thus, there is a real necessity to compile the data already described in the literature, obtained from tests in situ, in vivo and in vitro, derived from simulation experiments, occupational exposure or environmental disasters, in order to produce a report with the main effects already described for that class of pollutant. This review article intends to address the following issues: toxicity, cytotoxicity, genotoxicity, mutagenicity, teratogenicity and carcinogenicity of PAHs, besides information about estrogenicity and metabolism of these substances. In this context, it will be also presented the test systems that better responded to the assessments of the PAHs effects, in an attempt to show the most sensitive and efficient organisms to detect the contamination of these agents. © 2009 by Nova Science Publishers, Inc. All rights reserved.